Comparison of dexmedetomidine with chloral hydrate as sedatives for pediatric patients: A systematic review and meta-analysis. Issue 31 (31st July 2020) - Lian, Xianghong; Lin, Yunzhu; Luo, Ting; Yuan, Hongbo; Chen, Yuan
Abstract: Background: Dexmedetomidine (Dex) and chloral hydrate (CH) are the most frequently used sedative agents in pediatric patients. We aimed to systematically review the literature comparing the efficacy and safety of Dex and CH for sedation in pediatric patients. Methods: Seven electronic databases and 3 clinical trial registry platforms were searched for articles published prior to October 2019. Randomized controlled trials (RCTs) evaluating the efficacy and safety of Dex versus CH for sedation in children were examined by 2 reviewers. The extracted information included the success rate of sedation, sedation latency, sedation duration, sedation recovery time, and adverse events. Moreover, the extracted data included 5 subgroups: the effects of 1, 1.5, 2, 2.5, and 3 μg/kg doses of Dex were compared with the effect of CH on the success rate of sedation. We also formed separate subgroups for different types of adverse events (incidence of vomiting, hypotension, bradycardia, etc). The outcomes were analyzed by Review Manager 5.3 software and are expressed as relative risks (RR) or the mean difference (MD) with the 95% confidence interval (CI). Heterogeneity was assessed with I-squared ( I 2 ) statistics. Results: A total of 15 RCTs involving 2128 children with Dex versus CH for sedation were included in the meta-analysis. The dose range of Dex ranged from 1 to 3 μg/kg. Compared with CH, the Dex group had a significantly higher success rate of sedation (RR = 1.14, 95% CI [1.05, 1.25], I 2  = 79%, P  = .003). Additionally, subgroup analysis revealed that there was no significant difference in the success rate of sedation between the CH group and the 1, 1.5, 2.5, and 3 μg/kg Dex groups; only the 2 μg/kg Dex group had a significantly higher success rate than the CH group (RR = 1.15, 95% CI [1.03, 1.29], I 2  = 80%, P  = .02). There was no significant difference in the number of subjects who required 2 doses or the duration of sedation between the CH and Dex groups. Furthermore, compared with the Dex group, the CH group had a significantly longer sedation latency (MD = –3.54, 95% CI [–5.94, –1.15], I 2  = 95%, P  = .004), sedation recovery time (MD = –30.08, 95% CI [–46.77, –13.39], I 2  = 99%, P  = .0004), and total time from sedative administration to discharge (MD = –12.73, 95% CI [–15.48, –9.97], I 2  = 0%, P  < .05), as well as a higher number of adverse events in total (RR = 0.25, 95% CI [0.11, 0.61], I 2  = 89%, P  = .002). Moreover, the subgroup analysis of adverse events revealed that CH was associated with higher risks of vomiting (RR = 0.07, 95% CI [0.03, 0.17], I 2  = 0%, P  < .0001), crying or resisting (RR = 0.22, 95% CI [0.07, 0.71], I 2  = 60%, P  = .01), and cough (RR = 0.15, 95% CI [0.05, 0.44], I 2  = 0%, P  = .0006); there was no significant difference in the risk of hypotension, supplemental oxygen, or respiratory events between CH and Dex. However, Dex was associated with a higher risk of bradycardia (RR = 4.08, 95% CI [1.63, 10.21], I 2  = 0%, P  = .003). Conclusions: Dex is an appropriate effective alternative to CH for sedation in pediatrics. However, considering the possibility of bradycardia, Dex should be used with caution.